Effect of different ionic profiles of inland saline water on growth and agar characteristics of gracilaria cliftonii (Withell, Miller & Kraft, 1994) - Kumar, Vivek (Curtin University, 2008)
Salinity caused by the mobilisation of geologically stored salt through rising water tables is a major problem in Western Australia. Damage is occurring to aquatic and terrestrial ecosystems, affecting the profitability of agricultural land. However, the resultant inland saline water-bodies with an ionic composition similar to ocean water have the potential to be used for seaweed cultivation. Seaweed cultivation can mitigate the cost of land rehabilitation by making profitable use of saline wastewaters.A series of laboratory trials were conducted to identify the conditions necessary for successful Gracilaria cliftonii cultivation in inland saline water (ISW) and modify the agar extraction process for G. cliftonii to optimise agar yield and properties. This was accomplished by culturing G. cliftonii with different nutrients in ISW, with or without K[superscript]+ fortification and investigating the respective effects on chemical composition, physicochemical properties and agar characteristics. To identify the process required for optimum agar yield and quality from G. cliftonii, the effect of modifying some extraction process variables such as alkali concentration, soaking time and temperature, heating time, seaweed-water ratio, extraction time and temperature was investigated.These trials demonstrated that with the selection of appropriate nutrient media and culture conditions G. cliftonii can be successfully grown in ISW. To achieve higher growth rates of G. cliftonii, it is necessary to fortify ISW with K[superscript]+. The addition of nutrients to ISW and different ionic profiles of ISW had significant positive effects on chemical composition, physicochemical properties and agar characteristics. Agar yield, gel strength, melting point, gelling temperature and sulphate content were found to be a function of G. cliftonii life stages. Modification of alkali treatment with variable alkali concentration (0.3 to 5 %), soaking time and heating time had detrimental effect on agar yield resulting in significant agar loss but improved agar quality from G. cliftonii. However, agar quality can be improved by modifying extraction process variables like soaking time and temperature, seaweed to water ratio, extraction time and temperature without agar loss.